Biomass steam gasification of sugarcane leftover for green diesel production - Chatrattanawet, Narissara; Kanjanasorn, Worameth; Authayanun, Suthida; Saebea, Dang; Patcharavorachot, Yaneeporn (My University, 2018)
Biomass gasification is one of attractive processes for syngas production. In this research, sugarcane leftover is selected to use as feedstock. The produced gas has a purpose to use for green liquid fuels production through Fischer-Tropsch process. Consequently, this search aims to develop the model of syngas production from sugarcane leftover by using AspenPlus™ simulation software. In order to obtain syngas that suitable for producing liquid fuel, the content of some contaminants, i.e., CO2 and H2S must be concerned and thus, this process should be integrated with gas cleaning. The simulation was performed by using steam as gasifying agent. The effect of operating conditions in gasifier was also examined to find optimal conditions that provide the highest cold gas efficiency. The results showed that syngas content increases significantly with an increase in temperature and it reaches a stable at temperature higher than 750 °C. The optimal steam to biomass molar ratio is 0.6. Moreover, the absorption process by monoethanolamine (MEA) was studied to reduce H2S in syngas (below 0.1 mg/Nm3). Under this requirement, it was found that the optimal operating condition of adsorber is pressure of 40 bar and tray number of 10 by using MEA molar flow rate of 325 kmol/h.